On Antiperiodic Boundary Value Problems for Higher-Order Fractional Differential Equations - Ahmed Alsaedi; Bashir Ahmad; Afrah Assolami (Abstract and Applied Analysis)
We study an antiperiodic boundary value problem of nonlinear fractional differential equations of order q∈(4,5]. Some existence results are obtained by applying some standard tools of fixed-point theory. We show that solutions for lower-order anti-periodic fractional boundary value problems follow from the solution of the problem at hand. Our results are new and generalize the existing results on anti-periodic fractional boundary value problems. The paper concludes with some illustrating examples.